Modeling of the slab heating process in a walking beam reheating furnace for process optimization. (October 2017) - Tang, Guangwu; Wu, Bin; Bai, Dengqi; Wang, Yufeng; Bodnar, Rick; Zhou, Chenn Q.
Highlights: A new modeling methodology is proposed to optimize reheating furnace operation. Industrial experiment was conducted under typical operating conditions. The CFD models are validated with industrial experiment. The dynamic slab reheating process has been revealed using 3D CFD model. The proposed methodology is efficient in process optimization applications. Abstract: A new methodology involving the integration of a three-dimensional (3D) Computational Fluid Dynamics (CFD) model and a two-dimensional (2D) heat transfer model for the study of the slab reheating process in a walking beam reheating furnace has been proposed. A comprehensive 3D CFD model has been developed to simulate the flow characteristics, combustion process and multi-mode heat transfer phenomena inside an industrial slab reheating furnace. A customized 2D heat transfer model for the slab reheating process has also been developed based on the finite difference method. The simulation results from the 3D CFD model provide detailed heat transfer boundary conditions for the 2D heat transfer model. Instrumented slab trials were conducted under typical operating conditions of the furnace and the results were used to calibrate the 2D model. By comparing the slab temperatures measured from the instrumented slab trials and those predicted using the models, it was demonstrated that the 3D CFD and 2D heat transfer models predict the reheating process reasonably well. The proposed methodology is fairly easy to be used by mill engineers for trouble shooting and optimizing of the slab reheating process.